OPTIMALISASI PERMAINAN MONOPOLI SEBAGAI ALAT PENGEMBANGAN PSIKOSOSIAL DAN KEPERCAYAAN DIRI SISWA SD - Muthoharoh, Maratul; Rejeki, Asri (Universitas Tanjungpura, 2024)
The purpose of this study is to evaluate the effectiveness of the Monopoly game as an intervention to enhance self-confidence in fourth-grade students at SD NU Nurul Ishlah. This research employs a pre-experimental design with a